DINAMIKA PERGAULAN LINTAS KOMUNITAS GENG MOTOR BERDAMPAK PADA KEHIDUPAN MASYARAKAT DI PULO BRAYAN KOTA, KECAMATAN MEDAN BARAT, KOTA MEDAN - Asianna Manik; Daniel David Sidebang; Delila Maya Sari Siregar; Shelly Elprida Gajahmanik; Sri Yunita; Jamaludin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to determine the dynamics of cross-community motorcycle gang relationships that have an impact on the lives of people in Pulo Brayan City, West Medan District, Medan City. Motorcycle gangs are defined as a group of teenagers whose members are always together regularly, and they determine their own membership criteria. The actions of motorcycle gangs themselves refer to teenage acquaintances, because they have symptoms of social illness (pathology) in children that cause deviant behavior. This juvenile delinquency occurs due to various things such as environmental factors, and social relationship factors with the surrounding community. The method used in this study is a qualitative method using a descriptive approach. While the data collection techniques used are observation and interviews. The results of the study show that Based on the results of the research that we have done, the brutal actions carried out by motorcycle gangs will not only cause fear among the community, but can also create material losses and casualties. The activities they often do can be brawls, speeding, fights between rival gangs pioneered by the leader.